Educational Attainment and Returns to Education in Germany: An Analysis by Subject of Degree, Gender and Region - Andreas Ammermüller; Andrea Maria Weber (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
This paper presents evidence on the development of educational attainment and its returns on the labor market in Germany in the time period 1985-2002. Returns to education are estimated using Mincer equations. We analyze microcensus data in addition to GSOEP data, which allows estimating returns to tertiary education separately by subject of degree for the first time for Germany in such detail. The data indicate an educational expansion, especially for women in West Germany, which is coherent with the relatively high returns to this group. One interesting finding is that each gender reaches the highest returns in those fields of study where its shares are relatively high. For women this is in the fields of studies to become teacher, while men lead in law, business and economics and engineering. Additionally, the returns are higher for most degree subjects in West than in East Germany, especially for women.
Keywords: 330; Bildungsertrag; Deutschland